2016
DOI: 10.1097/sla.0000000000001375
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Resection of Clipped Node Decreases the False-negative Rate of Sentinel Lymph Node Surgery in Patients Presenting With Node-positive Breast Cancer (T0–T4, N1–N2) Who Receive Neoadjuvant Chemotherapy

Abstract: Background The American College of Surgeons Oncology Group Z1071 trial reported a false negative rate (FNR) of 12.6% with sentinel lymph node (SLN) surgery after neoadjuvant chemotherapy in women presenting with node-positive breast cancer. One proposed method to decrease the FNR is clip placement in the positive node at initial diagnosis with confirmation of clipped node resection at surgery. Methods Z1071 was a multi-institutional trial in which women with clinical T0-4,N1-2,M0 breast cancer underwent SLN … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
250
1
9

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 405 publications
(269 citation statements)
references
References 22 publications
(17 reference statements)
9
250
1
9
Order By: Relevance
“…Ve studii Boughey et al [7] byl znovu prozkoumán soubor studie Z1071 stran nalezení klipu v SLN po operaci. Uzliny, kde bylo vysloveno podezření na infiltraci před operací, musely být bio pticky verifikovány, vložení klipu do uzliny však nebylo podmínkou.…”
Section: Značení Uzlin Uhlíkemunclassified
See 1 more Smart Citation
“…Ve studii Boughey et al [7] byl znovu prozkoumán soubor studie Z1071 stran nalezení klipu v SLN po operaci. Uzliny, kde bylo vysloveno podezření na infiltraci před operací, musely být bio pticky verifikovány, vložení klipu do uzliny však nebylo podmínkou.…”
Section: Značení Uzlin Uhlíkemunclassified
“…Falešná negativita (tedy podíl případů, kdy byla nalezena infiltrace v jiné než označené uzlině -metoda nebyla kombinována s bio psií SLN) činila 7 %, což je rovněž méně než zmíněných 10 %. Studie se však ve výsledku potý-kala se třemi problémy: tivita metody (tedy že při negativitě uzliny s klipem a SLN byla nalezena infiltrace v uzlině v preparátu z AD) činila ve studii z MD Anderson 4,2 % [11] a ve studii Boughey et al 6,8 % [7]. Možnosti dalšího značení uzlin s klipem jsou rozebrány níže.…”
Section: Závěrunclassified
“…For instance, in ACOSOG Z1071, despite the use of dual tracer mapping and excision of at least two SLNs, the false-negative rate (FNR) for SLNB after NAC for previously cN1 patients remained unacceptably high ([10%) unless the axillary lymph node sampled before NAC was resected. 8 If the clipped node was excised, the FNR dropped to 6.8%. These data suggest that AUS should be considered for patients undergoing NAC to improve the accuracy of the subsequent SLNB and to maintain an acceptable FNR.…”
mentioning
confidence: 99%
“…While it was not required in the Mamtani et al study, adjuvant findings from Z1071 showed a potential FNR of 9.8 % if axillary ultrasound had been used after NAC, suggesting that axillary ultrasound should be considered to improve accuracy of SLNB in this setting. 10 The group from MSKCC has shown that, in experienced hands, using dual tracers and excising palpably abnormal LNs during SLNB allows for the removal of C3 SLNs in approximately 86 % of qualified patients and, ultimately, an acceptably low FNR (\10 %). Although not used in all studies, clips were placed in 203 patients enrolled in the Z1071 trial.…”
mentioning
confidence: 99%